Unbound vitamin D concentrations are not decreased in critically ill patients. Issue 1 (20th January 2022) - Palmer, David; Soule, Steven; Gaddam, Ravinder R.; Elder, Peter; Chambers, Stephen; Doogue, Matthew
Abstract: Background: Free concentrations of highly protein bound hormones, such as cortisol and thyroxine, are unchanged in critical illness despite substantial decreases in total concentration. Total 25‐hydroxyvitamin D (25(OH)D) concentration is decreased in critical illness, but the free concentration of 25(OH)D has had less attention. Aim: To compare total and calculated free 25(OH)D concentrations in critically ill patients with healthy controls. Methods: In this case‐control study, 38 patients with critical illness were compared with 68 healthy controls; 25(OH)D was measured by liquid chromatography tandem mass spectrometry (LCMS/MS) and vitamin D binding protein (VDBP) by direct sandwich enzyme‐linked immunosorbent assay. Total and calculated free 25(OH)D concentrations were compared using unpaired t ‐tests. Results: Total 25(OH)D concentrations were significantly lower in critically ill patients than controls (37 (95% confidence interval 31–43) vs 57 (53–60) nmol/L). Calculated free concentrations of 25(OH)D were not lower in critically ill patients than healthy controls (26 (22–29) vs 19 (18–20) pmol/L). Conclusions: Calculated free 25(OH)D concentrations are not decreased in critical illness. Measuring total 25(OH)D concentrations in patients with critical illness potentially underestimates vitamin D and overestimates the number of patients who are deficient in vitamin D.